The Role of Environmental Performances in Determining Financial Performances through Corporate Social Responsibility - Alya Susanto; Shiddiq Nur Rahardjo (Universitas Ahmad Dahlan, 2022)
This study was conducted to analyze the effect of environmental performance on financial performance with CSR disclosure as an intervening variable. The environmental performance was measured by using PROPER score, CSR disclosure was measured by the Global Reporting Initiative index, and financial performance was measured by using earning per share. Using purposive sampling method, this research took 89 samples from manufacturing companies listed in the Indonesia Stock Exchange that were granted PROPER by the Ministry of Environment and Forestry within the years of 2017-2019. The secondary data documented from companies' annual reports were used to test four hypotheses. The tests were conducted by using linnear regression and path analysis. The results of the analysis showed that environmental performance postively effecting CSR disclosure and CSR disclosure financial performance. However, this study did not find any significant effect of environmental performance on financial performance. It did not find CSR reporting's role as an intervening variable is unable to affect the environmental performance's impact towards financial performance.